Effects of the financial crisis on the turkish banking sector : a research on turkısh bankıng crısıs in 2000-2001 (International Journal of Scientific Research and Management (IJSRM), 2020)
The objective of this paper is to give a theoretical structure that incorporates the inward development and elements of money related markets and organizations hypothesis keeping in mind the end goal to look at how the financial market and the managing an account part create pointers that influence financial development in Turkey. Incredibly, the choice of capital putting resources into request to obstruction against different sorts of dangers is a noteworthy issue for the banks. At this stage, an essential strategy to decide stretch testing is imperative whether the capital proportions of the banks are satisfactory or not. The financial crisis of 2000-2001 was turned out to be devastating for Turkey after the plenitude of cash peg around the same time. The emergency being referred to originated from the deficient usage of controls, the insufficient profundity of the capital markets, the absence of evaluation of hazard, extreme loaning to consolidated establishments by national banks, confined financing costs, observed outside trade operations, constrained remote resource holding, the absence of rivalry, obstructions to remote section and high liquidity, endless swelling and a shortfall to be determined of installments. Bank performance is one of the vital issues for the healthy functioning of the Turkish economy. I use surrogate scenarios to test flexibility of the banking sector. In this research I check how much banking sector is flexible to external shocks under the planned scenarios. In this paper you can find so many objectives mean how you can examine your performance currently or in the past. The different panel data are collected that shows different perspective and views about the functionalism of the banking sector before and after the financial and economic crisis.